1995
DOI: 10.20870/productions-animales.1995.8.1.4105
|View full text |Cite
|
Sign up to set email alerts
|

Les effets de la lactation sur les performances de reproduction chez la lapine

Abstract: La lapine peut être fécondée aussitôt après la mise bas ou tout au long de la lactation, et être simultanément gravide et allaitante. Néanmoins, la réceptivité des femelles est variable au cours de la lactation : elle est maximale aussitôt après la mise bas (proche de 100 %) et minimale 3-5 jours après (40-65 %). Bien que les résultats expérimentaux concernant les effets de la lactation sur le taux d’ovulation et la mortalité embryonnaire soient parfois contradictoires, la fertilité et la prolificité des lapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Theau-Clément and Roustan (1992) showed that there was a particularly strong inverse relationship between lactation and reproductive function. During lactation there are high prolactin levels (Fuchs et al, 1984) that exert a hormonal antagonism on gonadotrophin release (Fortun-Lamothe and Bolet, 1995) thus inhibiting ovarian follicle development (Hamada et al, 1980).…”
Section: Artificial Inseminationmentioning
confidence: 99%
“…Theau-Clément and Roustan (1992) showed that there was a particularly strong inverse relationship between lactation and reproductive function. During lactation there are high prolactin levels (Fuchs et al, 1984) that exert a hormonal antagonism on gonadotrophin release (Fortun-Lamothe and Bolet, 1995) thus inhibiting ovarian follicle development (Hamada et al, 1980).…”
Section: Artificial Inseminationmentioning
confidence: 99%